A Excel for Accounting Assistance as the Solution for SME PT. JAB Surabaya - Titis Puspitaningrum Dewi Kartika; Nosy Yodi Metana; Sri Lestari Kurniawati (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2019)
Several studies suggested that most of Small and Medium Enterprises (SMEs) only noted the amount of money received and expended, the amount of bought and sold goods, and the amount of accounts receivable/debt. However, the note is functioned as reminder but not supported with the format desired by the banks. Even though, they are still able to know the amount of final capital each year which is almost the same as if we took a note by using accounting system. Therefore, Small and Medium Enterprises (SMEs) are directed through assistance to start taking notes of its business activities in accordance with the Accounting Standards Entities of Micro, Small and Medium Enterprises (SAK EMKM) simply and completely as needed. Basically, the partner's problem in this assistance was due to the accounting administration of financial management at PT. JAB which is not properly arranged such as the determination of HPP. This SME produces coffee powder, chocolate and green tea beverages. It reaches income of Rp. 50.000.000,- per month with the total 3-5 employees and has carried out bookkeeping which is currently experiencing loss. It has already made an excel financial report but in determining HPP, the process costs are not taken into account so that this has no basis. The result of this assistance is the establishment of financial statement which is correct and appropriate in accordance with SAK EMKM. This study is finally able to solve the problem in determining the amount of HPP due to the lack of synchronization between the production data and accounting department. In addition, this study successfully minimizes errors in determining the amount of inventory which affects the error in determining HPP. The problem faced by every SME must be different so that we are expected to provide assistance in making financial reports.